ARTICLE WRITING STRATEGIES THROUGH ONLINE LEARNING ON EDUCATIONAL RESEARCH - Ervina Maryati; Rensi Kumala Sari (Fakultas Keguruan dan Ilmu Pendidikan, 2021)
AbstractThis article aims to analyze the strategies of writing articles by students through online learning on the educational research subject. Internet usage, online journals, knowing the problem to research, focus, and diligently consult every writing to the supervisor. In this article, the author applies descriptive qualitative research methods and interview techniques. The process of writing this article includes several steps such as conducting interviews, identifying, and documentation to collect data. This article is to help readers easier to understand the strategy of writing articles through online learning on educational research subjects.Keyword: writing article strategies, internet, online journals, knowing the problem